2005
DOI: 10.1002/tox.20116
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized liquid extraction of toxins from cyanobacterial cells

Abstract: The suitability of pressurized liquid extraction (PLE) of cyanotoxins from cells was investigated. The stability of cyanotoxins (MCYST-RR, MCYST-LR, and anatoxin-a) was evaluated at nine combinations of pressure and temperature (7, 10, and 14 MPa and 60 degrees C, 80 degrees C and 100 degrees C) using 75% (v/v) methanol in water (MeOH) as solvent. Additional experiments investigated the stability of cyanotoxins when water was used as solvent (at a pressure of 14 MPa and a temperature of 40 degrees C, 50 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…ASE conditions, originally developed for the analysis of cyanotoxins in culture [27], were used for microcystins in sediments. Each stainless-steel extraction cell (33 mL) was lined with a cellulose filter and packed with sediment mixed with Hydromatrix TM (Varian, Mississauga, ON, Canada).…”
Section: Extraction Of Cyanotoxins From Sedimentsmentioning
confidence: 99%
“…ASE conditions, originally developed for the analysis of cyanotoxins in culture [27], were used for microcystins in sediments. Each stainless-steel extraction cell (33 mL) was lined with a cellulose filter and packed with sediment mixed with Hydromatrix TM (Varian, Mississauga, ON, Canada).…”
Section: Extraction Of Cyanotoxins From Sedimentsmentioning
confidence: 99%
“…The solution was then evaporated and pulled through a Sep-Pak C18 column and washed with 20% methanol. MCs were eluted with 90% methanol containing 0.1% TFA according to previously published methods (Harada et al 1988;Aranda-Rodriguez et al 2005;Qi et al 2009). Concentrations of MCs in the extracts were analyzed by high performance liquid chromatography (HPLC) (Agilent 1100 Series, Agilent Technologies, Waldbronn, Germany) equipped with a Zorbax Eclipse SB-C18 column (250 mm 9 4.6 mm, 5 lm, Agilent Technologies).…”
Section: Collection Of Cyanobacteria and Identification And Quantificmentioning
confidence: 99%
“…Analyses of extracts were performed according to Aranda-Rodriguez et al (2005) using an HPLC (Agilent 1100 Series, Agilent Technologies, USA) with a Zorbax Eclipse SB-C18 column (250 mm 9 4.6 mm, 5 lm, Agilent Technologies). MC-LR concentration in test solutions was monitored periodically and the results indicated that there were no remarkable differences between the measured and added MC-LR concentrations in test solutions during the experimental period (Table 1).…”
Section: Microcystin Analysismentioning
confidence: 99%